2023
DOI: 10.1007/s40588-023-00193-7
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Parasites in Feral Animals Commonly Consumed in Australia — Is There a Risk?

Abstract: Purpose of Review Consumption of wild game meat is traditionally associated with rural, remote and poor areas around the world, but there has been a recent rise in the consumption of wild game meat in urban and higher socio-economic regions such as Australia. Along with its unique animal fauna, Australia has a wide diversity of feral animals, many of which are hunted for food, although little is known about the levels of consumption of this meat across Australia. Corresponding with this is the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Raising awareness among medical practitioners of the most common and serious medical conditions that occur in immigrant groups from different geographic regions is important for early diagnosis and treatment of diseases that may initially be asymptomatic [1,62]. Additionally, culinary habits of countries change with the arrival of immigrants [63][64][65][66], leading to potential increases in infections with parasites in some groups. Barton et al [65] discussed the potential zoonotic risks of consuming feral animals in Australia especially given recent research which had reported L. serrata in rabbits [33], wallabies [32] and goats [67].…”
Section: The Need For Increased Awarenessmentioning
confidence: 99%
“…Raising awareness among medical practitioners of the most common and serious medical conditions that occur in immigrant groups from different geographic regions is important for early diagnosis and treatment of diseases that may initially be asymptomatic [1,62]. Additionally, culinary habits of countries change with the arrival of immigrants [63][64][65][66], leading to potential increases in infections with parasites in some groups. Barton et al [65] discussed the potential zoonotic risks of consuming feral animals in Australia especially given recent research which had reported L. serrata in rabbits [33], wallabies [32] and goats [67].…”
Section: The Need For Increased Awarenessmentioning
confidence: 99%